Judi Online Sebagai Cybercrime Serta Tantangan Penegakan Hukum Pidana di Era Digital: Antara Regulasi, Pembuktian, dan Ancaman Cybercrime - Seri Mughni Sulubara; Harry Fauzi; Bohari Muslim; M. Fadli Ferdiansyah Putra; Musmulyadi Musmulyadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Online gambling is a form of cybercrime that utilizes information and communication technology, especially the internet, as a medium to commit gambling crimes. Online gambling as a form of cybercrime has become an increasingly widespread phenomenon in line with the rapid development of information and communication technology. Gambling that was previously only known conventionally is now transforming into the digital realm by utilizing the internet as the main media. This research uses a theoretical study of online gambling as cybercrime. This research uses a qualitative approach with an analytical descriptive method. The types of data used are primary data in the form of laws and regulations (ITE Law, Criminal Code), online gambling case documents, official police reports, as well as academic literature and scientific articles related to cybercrime and online gambling. Meanwhile, secondary data is obtained from observation of the investigation process and law enforcement carried out by the cybercrime unit in the police. The data collection technique uses Library Research to collect secondary data relevant to cybercrime legal regulations and theories. The data analysis technique uses qualitative analysis techniques with a descriptive approach. Online gambling is expressly prohibited by Indonesian laws and regulations, especially through Law No. 11/2008 on Electronic Information and Transactions (ITE Law) and its amendments, such as Law No. 19/2016 and Law No. 1/2024. Article 27 paragraph (2) of the ITE Law prohibits any person from distributing, transmitting, or making accessible electronic information containing online gambling content, with imprisonment of up to 10 years and a maximum fine of IDR 10 billion in the latest amendment. In addition, the Criminal Code (KUHP) regulates gambling in general in Articles 303 and 303 bis, with criminal penalties that are also quite severe, although they do not specifically regulate online gambling. Law enforcement against online gambling faces various complex challenges. The existing regulations are still partial and not fully able to accommodate the cross-border and dynamic characteristics of cybercrime.Proof of online gambling cases relies heavily on electronic evidence that requires digital forensic expertise,such as imaging the perpetrator's device and server,as well as analyzing activity logs and electronic transactions